(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article discusses the story «Shayan Batyr» of the Semirechensk poet Esdaulet Kandekov. The legend «Shayan Batyr», belonging to the author’s oral poetry, did not attract the attention of prominent literary critics. Shayan Batyr, who was Suranci’s companion, participated in the wars against the Kokand, Russian military. The material for the study was the manuscripts of the legend «Shayan Batyr». In addition, this legend is compared with the epics «Alpamys», «Koblandy Batyr» and is considered a continuation of the epic tradition. The analyzed image of the hero and the event in the article can be considered as prerequisites for further indepth study of literary critics and historians.